Pengaruh Inflasi, Suku Bunga, Nilai Tukar Valas Dan Jumlah Uang Beredar Terhadap Profitabilitas Pada Perbankan Syariah Di Indonesia Periode 2005-2009 - Swandayani, Desi Marilin; Kusumaningtias, Rohmawati (AKRUAL: JURNAL AKUNTANSI, 2012)
Islamic finance quality show that performance improved, as indicated by the growing share of financing for the results of mudharabah and musyarakah. This study was conducted to examine the effect of macro economic indicators as measured by inflation, interest rates, foreign currency exchange rates and money supply to the ROA of Islamic Banking in Indonesia. Data analysis techniques used in this study is multiple linear regression analysis. F test results showed that simultaneous independent variables affect ROA. While the results of t tests showed that the inflation variable showed no significant effect on ROA. This is because, when inflation is high then the public more confidence in the Islamic banking compared with conventional banking. Predictive ability of four variables on ROA in this study by 19.8%, while the remaining 80.2% influenced by other factors that are not included in the research model.